Development of the core of an ICF-based instrument for the assessment of work capacity and guidance in return to work of employees on sick leave: a multidisciplinary modified Delphi study - Astrid de Wind; Birgit H. P. M. Donker-Cools; Lyanne Jansen; Clare H. Luymes; Sylvia J. van der Burg-Vermeulen; Shirley Oomens; Johannes R. Anema; Frederieke G. Schaafsma (BMC, 2022)
Abstract Background Several occupational health disciplines are involved in return to work guidance, implying that good interdisciplinary collaboration is important. A shared conceptual framework and a common language for the assessment of work capacity and guidance in return to work is expected to be at the benefit of appropriate and sustainable employability of sick employees. The International Classification of Functioning, Disability and Health (ICF) can be considered a shared conceptual framework and is also promising in terms of a common language. The purpose of the current study is to reach multidisciplinary consensus among occupational health professionals on the content of an ICF-based instrument for the assessment of work capacity and guidance in return to work. Methods To obtain multidisciplinary consensus we conducted a modified Delphi study among twelve occupational health experts, including four occupational physicians, four insurance physicians and four labour experts. The study included two e-mail rounds and two virtual meetings. In the consecutive rounds the experts assessed ICF items as well as a list of non-ICF-based work-related environmental factors on their relevance for the assessment of the work capacity and guidance in return to work together with their interpretability. Results The four consecutive Delphi rounds resulted in 20 items that are minimally needed for the assessment of the work capacity and return to work possibilities of employees on sick leave. The final list included six items on personal functioning, seven items on social functioning and seven items on physical functioning. Conclusions This set of items forms the core of an ICF-based instrument, which is expected to facilitate interdisciplinary and intradisciplinary communication because of the use of a shared conceptual framework. As such, it should be of help in the guidance in return to work of employees on sick leave and contribute to appropriate and sustainable employability.